Evaluation einer Professionalisierungsmaßnahme für inklusiven Englischunterricht Unterrichtsplanung und -durchführung vor dem Hintergrund des Universal Design for Learning - Böhm, Katharina (Interdisziplinäre Arbeiten zur Lehrer:innenbildung, 2023)
How can teacher training students be prepared better for their profession? This explorative study deals with the development and evaluation of a university-based professionalization measure in the context of the internship semester. The aim is to qualify prospective teachers successively for the planning and implementation of inclusive teaching in the subject English against the background of the Universal Design for Learning (UDL) and a planning guide. Among other findings, a significant increase in students' self-efficacy expectations related to inclusive instructional design was observed. The study makes a first contribution to researching the potential of inclusion-oriented professionalization measures against the background of the UDL in the school subject English.